Foreign Language Interpretation in Teaching Soloist Singing - Ujvárosi, Andrea (Central European Journal of Educational Research, 2021)
The problems of singing in the original language have become a special feature of the soloist training in the Central and Eastern Europe. The linguistic aspects of soloist training is put to the test by international expectation that regards authentic singing in the original language as a natural part of professional efficiency. In this present paper we are looking for the answers to two questions. First, we examined what factors determine the choice of the language for vocal interpretation. Our second goal is to give an overview of a specific segment of today’s Hungarian students’ population in higher education. We examined institutional, personal and curricular components for perfecting singing in the original language. The empirical study field of our research was Hungary’s higher education institutions of music in the 2016/17 term. Our researches were based on two methodological techniques. Among the higher education instructors of solo singers we conducted structured interviews and students from six higher educational institutions with this profile were the respondents of our questionnaire. The quantitative analysis of the research unequivocally represented the stronger demand of students for the training of linguistic interpretation. Our empirical research showed that the language efficiency of the solo singer students does not meet professional expectations. Pronunciation, comprehension, vocabulary, command of language and intonation are not utilized while singing and using the mirror effect of singing in a foreign language does not help perfect language knowledge either.